AGING AND NUTRIENT AVAILABILITY IMPACT HYDROGEN SULFIDE PRODUCTION AND SULFHYDROME PROFILES - Hine, C (Innov Aging, 2018)
Hydrogen Sulfide (H2S) serves as both an essential nutrient and selective pressure, resulting in cellular pathways for its production, utilization, and detoxification. Endogenously produced H2S stimulates metabolic-, stress resistance-, and longevity-associated pathways. Dietary restriction (DR), a potent lifespan extending intervention in a number of model organisms, enhances the enzymatic production of endogenous H2S. However, many of the downstream effects and molecular mechanisms driving the benefits of endogenous H2S remain unknown. Here, we examined one potential mechanism of action for endogenous H2S by detecting diet and aging induced changes in posttranslational-sulfhydryl modifications of protein thiols, termed sulfhydration. Similar to other posttranslational modifications, sulfhydration changes the activity, stability, and/or cellular localization of proteins. We tested the effect of diet on sulfhydration profiles in the liver and kidney, which are two of the strongest H2S producing organs in the body, via a biotin-thiol assay followed by LC-MS. We identified 1142 individual sulfhydrated proteins in the mouse liver, with 260 enriched by at least 2-fold under 1-week of 50% DR. In the mouse kidney, 1258 individual proteins were identified, with 262 enriched by at least 2-fold under DR. These enriched proteins fell into multiple pathways, including redox homeostasis and energy metabolism. Interestingly, in the brain, which is a relatively weak H2S producing organ, we discovered significant changes in the numbers and identities of sulfhydrated proteins. Future studies analyzing the functions of these sulfhydration events, combined with whole body sulfhydrome determination, will elucidate the extent to which controlling endogenous H2S production impacts health and physiology.